2021
DOI: 10.47626/1679-4435-2020-545
|View full text |Cite
|
Sign up to set email alerts
|

Work-related musculoskeletal disorders among schoolteachers

Abstract: Based on data from the Brazilian Institute of Geography and Statistics' National Household Sample Survey (Pnad), the authors apply a logistic model to measure if (and how much) early access to pensions decreases the probability of beneficiaries continuing to work. They also deploy two other strategies (Oaxaca-Blinder decomposition of wage differentials and propensity score weighting) to evaluate whether there is a decrease in productivity among pensioners that continue to work.Conservative estimates suggest a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Gender wise, this study result showed that there are more male suffers than female from upper back pain within the academic staff group, while among the nonacademic staff, there was no difference between male sufferers and female. This finding was in contrast with the finding of (Alias et al, 2020) and (Souza et al, 2021), where more female than male sufferers were reported respectively. The difference noted could be attributed to differences in sample sizes, difference in level of awareness and knowledge of work station ergonomics.…”
Section: Discussioncontrasting
confidence: 99%
“…Gender wise, this study result showed that there are more male suffers than female from upper back pain within the academic staff group, while among the nonacademic staff, there was no difference between male sufferers and female. This finding was in contrast with the finding of (Alias et al, 2020) and (Souza et al, 2021), where more female than male sufferers were reported respectively. The difference noted could be attributed to differences in sample sizes, difference in level of awareness and knowledge of work station ergonomics.…”
Section: Discussioncontrasting
confidence: 99%
“…Our study also found differences in MSD by age. People over 45 years of age have reported higher prevalences of MSD in different body parts, which may have a direct relationship with the human body’s aging process ( 45 ). However, our study found a higher prevalence in the lower and upper back areas in younger people (under 45 years of age), which could be related to lifestyle changes due to the lockdown imposed during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Several risk factors may contribute to the development of WRMSDs among dumper operators, such as individual characteristics—age and body mass index 12 , 13 , work-related factors—job demand and job control 14 , the physical environment of the mine, the ergonomics design of the dumper truck, and management practices 13 . Recent studies have identified the risk factors associated with WRMSDs among mine workers 15 18 .…”
Section: Introductionmentioning
confidence: 99%